2016
DOI: 10.4322/rbcv.2016.028
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência de Maedi-visna em rebanhos ovinos do estado do Maranhão, Brasil

Abstract: Apesar de ter sido relatada em vários estados, não há informação sobre o Vírus da Maedi Visna (MVV) no Maranhão, e com o crescimento de sua ovinocultura, aumenta o fluxo de animais de outras regiões. Com isso objetivou-se determinar a soroprevalência do MVV em rebanhos ovinos das três principais mesorregiões produtoras do estado do Maranhão, através da pesquisa das 1.495 amostras sanguíneas de ovinos, com idade superior a seis meses, pertencentes a 83 rebanhos de 23 municípios das mesorregiões Cento, Leste e N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…Data from Pernambuco revealed 5.2%, 1.07% and 0.26% seropositivity (OLIVEIRA et al, 2006;COSTA et al, 2007;MELO et al, 2016). In Maranhão and Ceará, seropositivity prevalence was 0.7% (TEIXEIRA et al, 2016b) and 31.67%, respectively (ALMEIDA et al, 2003). The fact that the latter study sampled sheep showing clinical signs of pneumonia likely explains the considerably higher seropositivity, as the other reports focused on herds lacking animals exhibiting symptoms compatible with MVV.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Pernambuco revealed 5.2%, 1.07% and 0.26% seropositivity (OLIVEIRA et al, 2006;COSTA et al, 2007;MELO et al, 2016). In Maranhão and Ceará, seropositivity prevalence was 0.7% (TEIXEIRA et al, 2016b) and 31.67%, respectively (ALMEIDA et al, 2003). The fact that the latter study sampled sheep showing clinical signs of pneumonia likely explains the considerably higher seropositivity, as the other reports focused on herds lacking animals exhibiting symptoms compatible with MVV.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 62.5% of the flocks were Santa Inês breed and without defined breed (SRD). It should be noted that to the extent that a flock passes through a breeding process, both goat and sheep, there is a trend of increasing prevalence of diseases, such as the lentiviruses (TEIXEIRA et al, 2016a;TEIXEIRA et al, 2016b). In the present study it was observed a predominance of SRD animals and without zootechnical bookkeeping, which may have influenced the low prevalence found.…”
Section: Discussionmentioning
confidence: 41%
“…However, the presence of reactive sheep in the north mesoregion may be due to the fact that this region had the highest concentration of sheep breeders in the study area, as well as the greatest number of cities, properties and animals sampled. Teixeira et al (2016) observed an overall prevalence of MVV of 0.7%, and prevalences of 0.5%, 0.7%…”
Section: Resultsmentioning
confidence: 88%